PROTEIN RESIDUE AND ORGANIC RESIDUE (FTIR) ANALYSIS OF STONE TOOLS FROM SITES HHOV337 AND HHOV467, FMA PROJECT 1840 MI06, NORTHEASTERN ALBERTA, CANADA - Yost, Chad; Cummings, Linda Scott (2009)
A total of 19 samples were submitted for protein residue analysis, and two samples for organic residue (FTIR) analysis from sites HhOv 337 and HhOv 467, located in northeastern Alberta, near the Athabasca River. Vegetation in the area is primarily a boreal forest ecosystem dominated by aspen, white spruce and black spruce. Wetlands are extensive in this region. Protein residue and organic residue (FTIR) analysis will provide data useful in determining tool function and plant and animal subsistence.